Problemas socioambientais e saúde no Vale do Taquari (RS): os atores sociais do campo da saúde e as políticas - Schwingel, Glademir (Universidade do Vale do Rio dos Sinos, 2014)
Sewage, production and management of liquid and solid waste, quality of water for human consumption are contemporary issues for big, mid-sized and small cities and appropriate solutions promote health and hinder disease. The present paper discusses the efficiency (or not) of these subjects in the definition of the public health policies, aligned with the forms of participation. Within the region of the 16th Regional Health Department, in Rio Grande do Sul, which comprises 37 cities, the perception of the health advisors of these small and mid-sized cities is assessed with respect to the priority setting in the organization of the local health systems. The aim is to detect the difficulties and potentialities for the development of sector and intersectoral public policies directed to the socio environmental issues coming from the acting parties in the municipal health councils. The questioning for the investigation is relevant since socio environmental matters and their relation with the healthcare field are in the agenda for discussion within the municipal health councils as a legitimate space in the legislative process. Has social control, by means of the municipal health councils, been addressing such issues? From the methodological point of view, to our analysis, the Municipal Health Plans have been evaluated as to their content regarding sewage, waste management and quality of water. Additionally, a group of advisors was interviewed, questioned about local public health policies deliberated in the municipal health council, their characteristics and determining elements. The condition of population health is an everyday concern of contemporary society, especially concerning the access to health care in secondary and tertiary levels. The Unified Health System (SUS) has brought considerable improvement over the past decades, especially in the primary health care, which reflects in the increase in the socio-sanitary indicators, even though the emphasis of the practices on healing procedures might be questioned. In this context, how does the priority setting in the municipal health councils of small and mid-sized cities take place? Are there recordings of some sort of concern about environmental issues and are actions to confront these problems addressed? The results indicate a tendency to prioritize disease and its repercussions within the community. The Municipal Health Plans are succinct or even omit the environmental issues, restricting to routine practices related to the sanitary and environment vigilance. The promotion of health and the relation environment-health is not present in the agenda of social control of this group of cities.
Keywords: Problemas socioambientais; Promoção da saúde; Participação social; Políticas públicas; Planejamento em saúde; Socio-environmental Issues; Promotion of health; Social participation; Public policies; Healthcare planning; ACCNPQ::Ciências Humanas::Sociologia